Respiratory physiology : the essentials - West, John B. [ (John Burnard)] (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2012)
Includes animations online - 8 in total - via thePoint to illustrate particularly challenging concepts. This title presents rationales for all questions, as well as explanations for each answer choice. It provides 82 essential-to-know, multiple-choice review questions which appear at the end of each chapter